Concevoir une formation en ligne à partir d’une étude sur les enjeux interculturels des ingénieurs - Mélanie Le Forestier (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This article presents the design process of an online course, called POMI (Preparing and Optimizing your International Mobility). This course is for engineering students but can be adapted to fit other curricula. The main pedagogical objective is to guide students in the development of an intercultural approach using their experience of international mobility. The specificity of this project is to link this engineering pedagogy with a research project that aims to identify beforehand what are the specific intercultural needs of the engineering programs and of the professional engineering context. We will firstly introduce our theoretical framework that tries to move away from several methodological biases which remain prevailing in interdisciplinary studies on intercultural communication. We will broaden the definition of interculturality beyond the aspect of internationalization of higher education in order to also consider other intercultural training and professional contexts. Our theoretical model of an intercultural approach has played an important role in the design of this online course, which will be introduced in the second part of the article. Finally, we will introduce the pedagogy that has been used for this project, which is also the pedagogical approach we recommend to teachers who want to incorporate an intercultural dimension in their pedagogical practices.